Lipoprotein apheresis in the management of severe hypercholesterolemia and of elevation of lipoprotein(a): current perspectives and patient selection - Julius U (Medical Devices: Evidence and Research, 2016)
Ulrich Julius Lipidology and Center for Extracorporeal Therapy, Department for Internal Medicine III, University Hospital Carl Gustav Carus at the Technische Universität Dresden, Dresden, Germany Abstract: This review reports the current situation with respect to therapeutic options (lifestyle and drugs) reducing the concentrations of atherogenic low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) (Lp[a]). Three lipoprotein apheresis (LA) principles have been realized: precipitation, filtration, and adsorption. Available LA methods are herein described in detail – major components, pumps, extracorporeal volume, treated volume, and anticoagulation. General features of all LA methods as well as pleotropic effects are elaborated. Indications for LA therapy are quoted: homozygous familial hypercholesterolemia (HCH), severe HCH, and isolated elevation of Lp(a) and progress of atherosclerotic disease. A major focus is on the evidence of the effect of LA on cardiovascular outcome data, and the most important publications are cited in this context. The best studies have been performed in patients with elevated Lp(a) in whom cardiovascular events were reduced by more than 80%. Major adverse effects and contraindications are listed. The impact of an LA therapy on patient quality of life and the requirements they have to fulfill are also highlighted. Finally, the future role of LA in treating high-risk patients with high LDL-C and/or high Lp(a) is discussed. It is probable that the significance of LA for treating patients with elevated LDL-C will decrease (with the exception of homozygous familial HCH) due to the application of PCSK9 inhibitors. The antisense oligonucleotide against apolipoprotein(a) could replace LA in patients with high Lp(a), provided positive outcome data are generated. Keywords: LDL cholesterol, lipoprotein(a), lipid-lowering therapy, lipoprotein apheresis, cardiovascular outcome